Low on‐state voltage and saturation current Trench Insulated Gate Bipolar Transistor with integrated Zener diode. Issue 24 (1st November 2017) - Li, Ping; Cheng, Junji; Chen, Xingbi
Abstract : A novel Trench Insulated Gate Bipolar Transistor is proposed, where an integrated Zener diode is introduced. When the anode voltage becomes relatively high, the Zener diode could automatically clamp the potential of the carrier stored layer which locates beneath the base region of the active trench nMOS. Then in the blocking‐state, the dose of the carrier stored layer could be as high as possible to reduce the on‐state voltage without affecting the breakdown voltage. In the on‐state, the drain‐to‐source voltage of the trench nMOS is also clamped, which helps to decrease the saturation current. Simulation results based on a 1.2 kV device show that, in comparison with the conventional one, the saturation current and the on‐state voltage are decreased by 42.8 and 43.1%, respectively.